Principles and practices of library science - Qureshi, Hasnain (Anmol Publications, 2006)
Contents of material: Concept and evolution. Rapid growth. Practical aspects. Social role. Plans and schemes. Laws for functionning. Role in education. Acadamic libraries. Popular libraries. Reference libraries. Special libraries. The personnel. Inter-library contacts. Models abroad.